I didn't find what I wanted - How do Developers Consume Information in Software Ecosystems Portals? - Parracho, Thiago de Moura; Zacarias, Rodrigo Oliveira; Seruffo, Marcos César da Rocha; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: Web portals play an important role within a Software Ecosystem (SECO), as they facilitate access to information and interaction among software developers over a common technological platform. Problem: Developers’ dissatisfaction with how information is presented on the SECO portal affects their engagement within the platform, causing a migration to consume information and interact in third-party channels, harming the SECO business model. Solution: This paper presents factors that influence developers’ search and information consumption on SECO technological platforms and suggestions that keystones can implement to increase engagement and transparency in their portals. IS Theory: This work was conceived under the Social Media Engagement Theory, regarding the transparency dimension in social interactions between users and platform technical resources. In this case, users are developers who seek knowledge about a SECO platform technology. Method: We conducted a survey with developers to understand their information consumption in SECO portals. Results were analyzed from quantitative and qualitative approaches. Summary of Results: From 50 responses, we identified three sets of categories associated with factors that influence developers on where to seek knowledge about a SECO technological platform (SECO portals or third-party channels) and we made three suggestions for keystones to increase engagement and transparency in their SECO portals. Contributions and Impact in the IS field: The main contribution is to favor developers’ engagement and transparency in information consumption and interaction within SECO portals. This study also contributes to the Grand Research Challenge “Transparency in Information Systems”.